THE IMPACT OF BUDGET ALLOCATION TO THE OFFICE OF THE COMPTROLLER GENERAL ON THE FIGHT AGAINST CORRUPTION: A SYSTEMATIC REVIEW FROM 2010 TO 2023 - Barrueto Pérez, María (2024)
The aim of the study was to investigate the impact of the budget allocated to the General Comptroller’s Office (CGR) on the incidence of corruption, using a systematic review covering the periods from 2010 to 2023. A qualitative methodology was employed, based on a systematic review of 8 academic articles and data from the World Bank, covering the ears 2013 to 2022. The analysis was conducted using a timeline to track trends over time. The study found that an adequate budget for the CGR significantly enhances its ability to prevent and detect acts of corruption. Funding enables the CGR to strengthen its internal control mechanisms, conduct more effective audits, and promote citizen participation in oversight. This positive impact on the fight against corruption aligns with the conclusions of García and Pérez (2016), who highlight the importance of budget allocation for the performance of oversight entities in Latin America, using World Bank data to support their analysis. KEYWORDS. General Comptroller, Corruption, Budget, Republic.